2015
DOI: 10.1155/2015/726085
|View full text |Cite
|
Sign up to set email alerts
|

Complete Remission of Anaplastic Thyroid Carcinoma after Concomitant Treatment with Docetaxel and Radiotherapy

Abstract: Anaplastic thyroid carcinoma (ATC) although rare is the most lethal form of thyroid cancer. The mortality rate for ATC is very high, with a median survival time of only 5 months; the survival rate at 1 year after diagnosis is <20%. Management of ATC is extremely difficult and rife with uncertainties. Herein, we describe a 75-year-old woman who presented with ATC and was successfully treated using concomitant treatment with docetaxel and high-dose radiotherapy. This case appears to be the first to have been rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…While various treatments have been tested and established, it has been difficult to achieve complete remission of anaplastic thyroid carcinoma. In the recent literature, 9 cases with complete remission within the observation period (at least over 9 months) of anaplastic thyroid carcinoma assessed by pathological examination and/or FDG-PET were reported in detail (Table 3) [146][147][148][149][150][151][152][153]. All the patients with complete remission were of stage IVB and underwent combined treatments of chemotherapy and radiotherapy.…”
Section: Complete Remission By Multimodal Treatments In Previous Repo...mentioning
confidence: 99%
“…While various treatments have been tested and established, it has been difficult to achieve complete remission of anaplastic thyroid carcinoma. In the recent literature, 9 cases with complete remission within the observation period (at least over 9 months) of anaplastic thyroid carcinoma assessed by pathological examination and/or FDG-PET were reported in detail (Table 3) [146][147][148][149][150][151][152][153]. All the patients with complete remission were of stage IVB and underwent combined treatments of chemotherapy and radiotherapy.…”
Section: Complete Remission By Multimodal Treatments In Previous Repo...mentioning
confidence: 99%
“…In particular, the advanced cancer subtype (ATC) has a poor prognosis owing to its resistance to treatment and aggressive behavior [5] , [6] . The total median survival is only a few months [6] , [7] .…”
Section: Introductionmentioning
confidence: 99%
“…Poorly differentiated cancers are often resistant to anti-cancer drugs; moreover, effective clinical guidelines for ATC are currently lacking [7] . However, recent evidence has shown that induction of the epithelial-mesenchymal transition (EMT) in cancer cells not only results in metastasis, but also serves as a major contributing factor in drug resistance [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…We report two well characterized, exceptional cases of complete pathological tumor response in advanced stage IVb and IVc ATC. Only five similar cases of ATC patients in complete pathologic tumor response have been reported to date (Table 2), none by querying the French reference network for advanced thyroid cancer's database (n= 386, unpublished data) [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…We report two well-characterized, exceptional cases of complete pathological tumor response in advanced stage IVb and IVc ATC. Only five similar cases of ATC patients in complete pathologic tumor response have been reported to date ( Table 2 ), none by querying the French reference network for advanced thyroid cancer’s database ( n = 386, unpublished data) ( 13 , 14 , 15 , 16 ). There was no difference between our patients and the previously reported cases regarding characteristics at diagnosis or therapeutic management, which was carried out according to standard guidelines ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%